NEGATIVE CONSEQUENCES IN THE CARDIOVASCULAR SYSTEM UNDER THE INFLUENCE OF ENERGY DRINKS - To’xtayeva N. X.; Bolqiyev S. A.; Eshbekova L. SH.; Hamdamov A.I.; Nazirov N. R (American Journals, 2024)
This article details the effect of one of the most popular non-alcoholic beverages on the functioning mechanism of the heart, muscle contraction power, pulse, blood composition. Due to an increase in energy drink consumption over the past decade, the number of energy drinks consumers has also increased significantly among those who turn to emergency calls. That is, an increase in the number of drinking poisoning, arrhythmia, blood pressure and heart rate occurs. We did research among our peers in order to track these effects.
Keywords: Energy drinks, caffeine, taurine, Cardiovascular Effects Arrhythmia, adrenaline, Baum and Weiss Research, Sugar, Insulin, Red Bull.